Speech by Brig. Gen. Dato' Prof. Dr. Kamarudin Hussin Vice Chancellor of UniMAP during Opening Ceremony MTUN Fortune Forum - Kamarudin, Hussin, Brig. Gen. Dato' Prof. Dr. (Universiti Malaysia Perlis, 2010)
Event was held at Penang, Malaysia.